2019
DOI: 10.1016/j.reactfunctpolym.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Bis[2-(methacryloyloxy)ethyl] phosphate radiografted into track-etched PVDF for uranium (VI) determination by means of cathodic stripping voltammetry

Abstract: We report the radiation grafting of bis [2-(methacryloyloxy)ethyl] phosphate (B2MP) through electron-beam onto PVDF films and through swift heavy ions (SHI) irradiations into the pores of track-etched PVDF membranes. Radiolytically produced radicals were studied using EPR. To adapt the radiation grafting protocol inside the nanopores of track-etched membranes, the electron-beam irradiated films at varying monomer concentrations, doses and solvent mixtures were first studied. It was found that track-etched memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…functionalised membrane fabrication and characterization. The functionalised track-etched PB2MP-g-PVDF membranes were fabricated as described in 4 and displayed in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…functionalised membrane fabrication and characterization. The functionalised track-etched PB2MP-g-PVDF membranes were fabricated as described in 4 and displayed in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Для обна-ружения ионов свинца и других тяжелых металлов в качестве рабочих электродов могут использоваться различные виды платформ, например, оксид графена, стеклоуглеродный электрод, углеродная паста диоксид титана/диоксид циркония, углеродные нанотрубки, полимеры и мембраны [7], тонкие углеродные пленки, наночастицы металлов. Кроме того, растет интерес к использованию трековых мембран (ТМ) в качестве двухэлектродного сенсора для обнаружения Pb (II), Hg (II), U (VI) [8][9][10].…”
Section: Introductionunclassified
“…Авторы [9] использовали прививку поли(4-винилпиридина) в нанопоры ПВДФ для улучшения обнаружения ионов ртути. ПВДФ ТМ также использовались для обнаружения урана (VI) в с использованием инверсионной вольтамперометрии после прививочной полимеризацией бис[2-(метакрилоилокси) этил]фосфата [8]. Кроме того, было найдено, что электроды, модифицированные композитом показа-ли значительный синергетический эффект в улучшении чувствительности, селективности и стабильности сенсоров [13].…”
Section: Introductionunclassified
“…For such purpose, materials based on carbon nanotubes [9], carbon thin film [10], graphene and graphene oxide [11], metal nanoparticles [11,12,13,14], and polymers and membranes [15,16,17] are used as WE. Moreover, the number of publications has been growing on the use of track-etched membranes (TeMs) based on polyvinylidene fluoride (PVDF) as a dual-electrode [18,19,20,21,22,23]. TeMs are thin (5–24 µm), light, and flexible polymeric films with pores with narrow pore-size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(4-vinyl pyridine) (P4VPy) grafted into PVDF was found to be effective in detection of mercury [19,26] with concentrations ng/L after 24 h of absorption and µg/L after 2 h of absorption. Penaeva et al [18] reported the electron-beam-induced graft polymerization of bis[2-(methacryloyloxy)ethyl] phosphate onto PVDF membrane for the detection of uranium (VI) in ppb concentrations from 20 to 100 ppb using square wave cathodic stripping voltammetry.…”
Section: Introductionmentioning
confidence: 99%